1993
DOI: 10.1111/j.1476-5381.1993.tb13433.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of a 5‐HT3 receptor which modulates the release of 5‐HT in the guinea‐pig brain

Abstract: 1 The aims of the present study were to confirm the modulation by 5-HT3 receptors of the electrically evoked release of tritium from slices preloaded with [3H]-5-HT of guinea-pig frontal cortex, hippocampus and hypothalamus, and to assess their functional role in 5-HT release. 2 The selective 5-HT3 agonist, 2-methyl-5-HT, introduced 8 min before the electrical stimulation, enhanced in a concentration-dependent manner the evoked release of [3H]-5-HT in the three brain regions studied. The 5-HT3 agonists, phenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…These data are confirmed by the observation that PBG failed to bind to 5-HT 3 R protein in isolated membranes. PBG showed no effect on 5-HT 3 Rs of guinea pig in functional assays (Butler et al, 1990;Blier and Bouchard, 1993). The antagonists metoclopramide and tropisetron are less active on the guinea pig 5-HT 3 R that on the receptors of mouse and human in electrophysiological and radioligand binding assays.…”
Section: Discussionmentioning
confidence: 92%
“…These data are confirmed by the observation that PBG failed to bind to 5-HT 3 R protein in isolated membranes. PBG showed no effect on 5-HT 3 Rs of guinea pig in functional assays (Butler et al, 1990;Blier and Bouchard, 1993). The antagonists metoclopramide and tropisetron are less active on the guinea pig 5-HT 3 R that on the receptors of mouse and human in electrophysiological and radioligand binding assays.…”
Section: Discussionmentioning
confidence: 92%
“…It is less possible that 2-methyl-5-HT acts as blocker of 5-HT transporter and increases outflow of radioactivity by preventing uptake of released 5-HT. 2-Methyl-5-HT-altered 5-HT outflow was also blocked by the 5-HT uptake blocker paroxetine in guinea-pig hypothalamic slices [29]. The effect of 2-methyl-5-HT on […”
Section: Mode Of Actionmentioning
confidence: 96%
“…Other study concluded that 5-HT 3 receptors in the hypothalamus influence 5-HT release as heteroreceptors [30]. Besides hypothalamus, it has been shown that 5-HT 3 receptor stimulation also evokes increase in electrically induced 5-HT release from guinea-pig cerebral cortex or hippocampus, brain areas containing serotonergic axon terminals [29,66].…”
Section: -Ht 3 Receptor-mediated 5-ht Release In the Raphe Nuclei: Fmentioning
confidence: 99%
“…5-H1' has been shown to exert a positive feedback on its own release via 5HT3 receptors in the hippocampus (Blier and Bouchard, 1993). It can also inhibit the release o f A C h from hippocampal ACh terminals via 5-HTTH or 5-H-r~ receptors (Maura and Raiteri, 1986;Muraniatsu et al, 1988;Harel-Dupas ec al., 1991), or stimulate this release through 5-HT receptors which remain to be defined (Ohue et al, 1992(Ohue et al, , 1993.…”
Section: Functional Implicationsmentioning
confidence: 99%